2018
DOI: 10.1093/mnras/sty397
|View full text |Cite
|
Sign up to set email alerts
|

Non-ideal magnetohydrodynamics on a moving mesh

Abstract: In certain astrophysical systems the commonly employed ideal magnetohydrodynamics (MHD) approximation breaks down. Here, we introduce novel explicit and implicit numerical schemes of ohmic resistivity terms in the moving-mesh code AREPO. We include these non-ideal terms for two MHD techniques: the Powell 8-wave formalism and a constrained transport scheme, which evolves the cell-centred magnetic vector potential. We test our implementation against problems of increasing complexity, such as one-and two-dimensio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 75 publications
4
123
0
Order By: Relevance
“…feedback from AGN, as shown by the comparison between non-radiative and "full physics" runs. Using a Lagrangian finite volume method, Marinacci et al (2015Marinacci et al ( , 2018a showed magnetic 2018field seeding and evolution with the "Illustris" subgrid model for galaxy formation, also including explicit diffusivity. They obtained μG magnetic fields in clusters when they included seeding from galaxy feedback (Fig.…”
Section: Cosmological Simulations Of Magnetic Fields In Galaxy Clustersmentioning
confidence: 99%
“…feedback from AGN, as shown by the comparison between non-radiative and "full physics" runs. Using a Lagrangian finite volume method, Marinacci et al (2015Marinacci et al ( , 2018a showed magnetic 2018field seeding and evolution with the "Illustris" subgrid model for galaxy formation, also including explicit diffusivity. They obtained μG magnetic fields in clusters when they included seeding from galaxy feedback (Fig.…”
Section: Cosmological Simulations Of Magnetic Fields In Galaxy Clustersmentioning
confidence: 99%
“…Similar configurations have also been used in the context of nonideal MHD to measure reconnection rates (see e.g. Marinacci et al 2018, and references therein).…”
Section: Current Sheet Problemmentioning
confidence: 99%
“…The implementation makes use of Arepo's MHD capabilities (Pakmor et al 2011;Pakmor & Springel 2013) and is the latest addition to a suite of non-ideal physics options in Arepo. These options already include effects such as isotropic viscosity (Muñoz et al 2013), cosmic ray transport (Pakmor et al 2016b;Pfrommer et al 2017), anisotropic heat conduction (Kannan et al 2016), Ohmic diffusion (Marinacci et al 2018) and radiation transport (Kannan et al 2019).…”
Section: Algorithmmentioning
confidence: 99%